The Influence of Leadership, Career Development, and Organizational Commitment on Employee Performance at the Education Office of Gresik Regency - Laila, Husnul; Sundjoto, Sundjoto; Rahayu, Sri (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to examine the influence of leadership, career development, and organizational commitment on employee performance at the Education Office of Gresik Regency. The research was conducted using a quantitative approach with a survey method involving employees from the Education Office as the sample. Data were collected through questionnaires and analyzed using statistical techniques, including regression analysis, to identify the relationships between the variables.The results of the study indicate that leadership significantly affects employee performance, with effective leadership enhancing employee motivation and performance. Career development programs also have a positive impact on employee performance, as they provide opportunities for skill enhancement and personal growth. Furthermore, organizational commitment was found to be a key factor in improving employee performance, as employees who are more committed tend to exhibit higher levels of job satisfaction and productivity.This study concludes that leadership, career development, and organizational commitment are critical factors that influence employee performance in the Education Office of Gresik Regency. The findings suggest that management should focus on improving these areas to optimize employee performance and contribute to the overall success of the organization.